PENGARUH KOMITMEN ORGANISASI, KAPASITAS SDM, PERAN INTERNAL AUDIT, DAN SISTEM INFORMASI AKUNTASI TERHADAP KUALITAS LAPORAN KEUANGAN PENGADILAN AGAMA SUMENEP - Wildan Affan Al Gifari; Ade Irma Suryani Lating; Riza Sufia Latifa; Moch Yusril Ihza Mahendra (Ekomania, 2024)
The Role of Internal Audit and Accounting Information Systems on the Quality of Financial Statements of the Suemenp Religious Court” is a quantitative study that aims to answer the formulation of problems related to the influence of organizational commitment, HR capacity, the role of internal audit and accounting information systems on the quality of financial statements. The research method used in this research is a quantitative approach. The analysis technique used is multiple linear regression analysis using SPSS 21 software. The number of samples in this study was 44 people using purposive sampling of all employees and employees of the Sumenep Religious Court. The data used in this study are primary data and data collection is done by distributing questionnaires. The results of research conducted based on the t-test show that the variables of organizational commitment and the role of internal audit have a significant effect on the quality of financial statements, each of which has a considerable value smaller than 0.05. In contrast, the variables of human resource capacity and accounting information systems do not affect the quality of financial statements, each of which has a significant value greater than 0.05.